CCAFS GSI-sponsored gender research informs Kenya Dairy NAMA to increase on-farm dairy productivity through private sector investment in gender-inclusive extension - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
GSI provided support to UNIQUE forestry and land use GmbH for a process of action research to ensure that the Kenya Dairy NAMA leverages best practices to deliver benefits to women and other marginalized groups at large scale. The Kenya Dairy NAMA includes “Increasing on-farm dairy productivity through private sector investment in gender-inclusive extension services and fodder supply” as one of four components, a result of GSI-sponsored research and consultations with the private sector.